Interactive Smart Tennis Ball Collecting Vehicle - Chen, Hung-Kuang; Dai, Jyun-Min (Recent Patents on Computer Science, 2017)
Background: As one of the most popular racket sports in the world, tennis usually takes a considerable amount of repetitive training that uses a great number of tennis balls. After the training, collecting the tennis balls is an annoying, time consuming, and labor taking task. To cope with such problem, a great number of tennis ball collectors such as the stroller-based, basket-based, and wheeler-based collectors were proposed, also described in various patents. However, existing tennis ball collectors mostly require manual operation. To eliminate human intervention, a recent trend is to automate the process by electronic devices. Methods: Our new collector combines a wheeler-based collector with a smart vehicle providing both automatic programmed route and interactive remote-controlled collection. To accommodate tennis balls of various sizes, the basic collector comprises two discs of resilient material attached with four springs. By cascading a number of basic ball collectors side-by-side with an axle through their center, we may extend the basic tennis ball collector from single channel to multiple channels. Results: In order to simulate the distribution of tennis balls after a practice session, 30 tennis balls are randomly distributed over a half court at the start of each test. In interactive navigation tests, the user is requested to collect the 30 tennis balls as soon as possible by controlling the vehicle through a smartphone. The test results showed that the amount of time taken to complete the interactive collection fall into the range of 4 to 15 minutes; on the other hand, the time taken to complete automatic preprogramed route collection is around 14 to 15 minutes. Conclusion: In comparison with traditional labor work that usually takes more than 15 minutes, our novel design greatly reduces the collection time and improves the user experience by changing the tennis ball collection from a dull and painful task to an interesting one.
Keywords: automatic control